Une communication politique 2.0 - Alexandre Eyries; Cassandra Poirier (Communication)
Political communication today has become a matter of academic interest even though it is too often identified with political marketing. The rise of information and communication technologies – notably media and social networks including Twitter - has transformed the media practices and communication policies of political parties. The authors compare the use made of Twitter in 2012 – in France and in Quebec - during the presidential and the provincial elections in order to measure it’s influence on the course of two campaigns and on their outcome.